Extended D3 Mesenterectomy in Small Bowel Cancer Treatment: Feasibility and Importance for Staging. First Results of a Prospective Clinical Trial - Erik Kjæstad; Espen Thiis‐Evensen; Bjørn Edwin; Arne Olav Bakka; Anne Helene Lilleaas; Yngve Thorsen; Johannes Kurt Schultz (World Journal of Surgery, 2026)
ABSTRACT Background There is no consensus on surgical techniques in small bowel cancer, particularly regarding the extent of lymph node dissection and strategic choices according to tumor localization and histological type. Clearance of central lymph node metastases can be challenging, especially when small intestinal neuroendocrine tumor (siNET) metastases give rise to fibrosis and desmoplasia around the cranial parts of the superior mesenteric vessels. The aim of this study was to assess the feasibility and staging implications of new techniques of central (D3) lymphadenectomy. Material and Methods The operative techniques in this prospective small bowel cancer cohort entailed central (D3) removal of all mesenteric tissue anterior and posterior to the superior mesenteric vessels up to the root of the mesentery. Preoperative 3D mapping of the vascular anatomy was performed to facilitate personalized surgery. A new resection classification was developed, based on bowel and mesentery involvement. Results Among the 86 patients included, D3 lymphadenectomy was performed in 74 (86%). Small bowel resection was done in 40 (54%), and ileocecal or ileocolic resection in 34 (46%). There were five (7%) reoperations (two (3%) anastomotic leaks) and no 30‐day mortality. At histopathology, 60 siNET (81%), 5 small bowel carcinomas, 3 metastases of other origin, 1 benign lesion, 3 lymphomas, and 2 gastrointestinal stromal tumors (GIST) were diagnosed. Lymph node count of 71 patients (one benign, two lymphomas not counted) showed mesenteric lymph node metastases in 62 (87%) (median lymph node yield 33). Metastases to the D3 volume were found in 31 (44%) (median D3 lymph node yield 13). In the siNET‐group, 28/60 (47%) had D3 metastases, suggested in standard preoperative investigations in 12 (43%). Of all positive siNET lymph nodes, 173/509 (34%) were localized in the D3 volume. Upper/middle ileal siNET were D3 positive in 19/29 (66%) versus in 9/31 (29%) of terminal ileal siNET. All patients had mesenterial R0 resections. Conclusions Central (D3) small bowel mesenterectomy can be performed with radicality and safety. The high proportion of central metastases that would remain in situ after traditional, less extensive (D2) surgery underlines the potential importance of D3 mesenterectomy for accurate staging and locoregional disease control. Subgroup analyses suggested differences in mesenteric dissemination between terminal ileal and more proximal small intestinal tumors.